EFEKTIVITAS TERAPI AIR HANGAT TERHADAP NYERI TULANG BELAKANG PADA IBU HAMIL - Sari, Endang; Radhia, Mekar Zenni; Zaini, Hanifa (Ensiklopedia of Journal, 2025)
Abstract: Spinal pain in pregnancy is a pregnancy problem that has become a phenomenon in the world today. Spinal pain in pregnancy is caused by hormonal, musculoskeletal changes and stress. Spinal pain in pregnancy if left untreated will impact the quality of life and daily activities of pregnant women. Management of spinal pain in pregnancy can include pharmacological and non-pharmacological. One of the non-pharmacological treatments for pain is warm water therapy. Objective Warm water therapy provides a relaxing effect, vasodilates blood vessels, removes metabolic waste that is no longer used, and reduces muscle spasms. Research methods: this research applies a type of quantitative research with a non-equivalent quasi-experimental design with one group pre test and post test design. A sample of 20 pregnant women who experienced spinal pain used a purposive sampling technique. This research instrument uses the Visual Analog Scale. Research result: Statistical tests using the paired t test on spinal pain before and after the intervention showed p value = 0.000 (0.14). This result shows the strong effectiveness of warm water therapy on spinal pain in pregnancy. Conclusion: The results of this study can be used as a reference for treating spinal pain in pregnancy. It is hoped that there will be further research regarding other non-pharmacological techniques for spinal pain in pregnancyKeywords: Pregnancy, Spinal Pain, Warm Water Therapy.